Méprise, Errance et Métaphore Paternelle dans American Pastoral de Philip Roth - Béatrice PIRE (E-REA)
This article reads American Pastoral within the theoretical framework of Lacan’s 1973/1974 seminar on « Les non-dupes errent » and Freud’s Psychopathology of Everyday Life. Following the tradition of postmodern writing, Roth’s novel explores two forms of errors, Zuckerman’s mistake regarding his reading of Levov and Levov’s own failure regarding his life. Fiction as failure or lapsus coincides with Lacan’s definition of truth, as ‘not-whole,’ unsuccessful and therefore a success. Merry is the character that errs and wanders most in the book, a Lacanian psychotic ‘non-dupe’ paradoxically helping to re-establish the repressed ‘name of the father’ or paternal metaphor in the end.